Cementless total hip arthroplasty with extended sliding trochanteric osteotomy for high congenital hip dislocation: A retrospective study. Issue 14 (April 2017) - Luo, Zhengliang; Chen, Min; Hu, Fei; Ni, Zhe; Ji, Xiaofeng; Zhang, Xiaoqi; Cheng, Peng; Shang, Xifu
Abstract : Abstract: Total hip arthroplasty (THA) for high congenital hip dislocation (CHD) is technically demanding. The purpose of this retrospective study was to evaluate the results of cementless THA combined with extended sliding trochanteric osteotomy. We also assessed whether chronic low back pain was relieved after surgery. The study included 19 patients (23 hips) with high CHD treated with cementless THA using extended sliding trochanteric osteotomy technique. Clinical and radiographic outcomes were evaluated. Harris Hip Score, WOMAC score, visual analog scale for low back pain and Trendelenburg sign were significantly improved ( P < 0.01) compared with the preoperative. Average limb-length discrepancy in the 15 unilateral hips was reduced from 38.2 ± 7.9 mm to 6.7 ± 4.1 mm ( P < 0.01). No dislocation, deep vein thrombosis, or infection occurred. Two patients (8.7%) developed sciatic nerve palsy. One (4.3%) developed symptomatic greater trochanteric bursitis. Two (8.7%) sustained proximal femur shaft fracture during implantation of the femoral component. All femoral components showed successful bony ingrowth at the final follow-up. No stem subsidence was detected. There was no acetabular loosening. Bony union of the reattached greater trochanter was obtained in all hips. Wire breakage occurred in 3 hips (13%). Cementless THA with extended sliding trochanteric osteotomy may be appropriate options for patients with high CHD.